Students’ Perceptions in Online Learning toward Reading Comprehension at Tenth Grade of SMA Negeri 1 Kota Jambi - Tino Purnomo; Yanti Ismiyati; Khidayatul Munawwaroh (Universitas Batanghari Jambi, 2021)
This study investigated the students’ perceptions in online learning toward reading comprehension at tenth grade of SMA Negeri 1 Kota Jambi. A quantitative research design was used in this study. The participants are 36 students from tenth grade MIPA 4 of SMA Negeri 1 Kota Jambi. The instruments used to collect the data were questionnaire. The questionnaire consisted of 30 statements. Google Form was used to obtain the data and the result was used to analyze the data. As a result of the study, the researcher concluded that the benefits of online reading have had a substantial effect on the knowledge of students’ vocabulary, and the students have strongly focused on the educational evaluation they read during online learning. The data reported the highest percentage is 56% of the students strongly agreed that online media supported their activity in reading during online learning. However, the lowest percentage is 5% of the students disagreed that online media supported their activity in reading during online learning. The results show that the mean and standard deviation between students’ perceptions in online learning toward reading comprehension are 77.00 mean and 16,696 standard deviation, which is the standard deviation is higher than the mean. It shows that students' perceptions are considered positive because most of the students agree that online learning helped them to improve their reading comprehensions skills.Keywords: Students’ Perception, Online Learning, Reading Comprehension.